Electrocatalytical of chlorophenoxycarboxylic acids at a protoporphyrin IX cobalt(III) chloride modified glassy carbon electrode - Chaiyasith, Suwan; Tangkuaram, Tanin; Chaiyasith, Pachernchai (My University, 2005)
Protoporphyrin IX cobalt(III) chloride (Co(ProP)Cl) was immobilized on a glassy carbon electrode (GCE) to facilitate the electrocatalytical determination of 2,4-dichlorophenoxycarboxylic acids (2,4-D) and three of its derivatives 2-(2,4-dichlorophenoxy) propionic acid (2,4-DP), 2-(2,4,5-trichlorophenoxy) propionic acid (2,4,5-TP) and 4-(2,4-dichlorophenoxy)butyric acid (2,4-DB) in aqueous solution. Co(ProP)Cl was immobilized by a spontaneous adsorption method. The electrocatalytic reduction peak of 2,4-D and its three derivatives was found at -1.12 V (vs. Ag/AgCl). Employing chronoamperometry, the highest limiting current was found for a modified GCE with 1 mM Co(ProP)Cl in acetonitrile|water (1:3; v/v) containing 0.1 M KCl at -1.15 V. Good linear response of the modified electrode was found in 10-400 μM for 2,4-D, 2,4-DP and 2,4,5-TP; and in 10-300 μM for 2,4-DB. The detection limits were estimated as 0.98, 1.14, 0.89, and 2.77 μM for 2,4-D, 2,4-DP, 2,4,5-TP and 2,4-DB, respectively. The lifetime of the Co(ProP)Cl-GCE was seven times for 2,4-D; eight times for 2,4,5-TP; and six times for 2,4-DP and 2,4-DB. © 2005 Elsevier B.V. All rights reserved.
Keywords: Chlorophenoxycarboxylic acids; Cyclic voltammetry; Electrocatalytic dechlorination; Protoporphyrin IX cobalt(III) chloride modified GCE electrode